Characterisation of circulating biomarkers before and after cardiac resynchronisation therapy and their role in predicting CRT response: the COVERT-HF study. Issue 2 (18th October 2018) - McAloon, Christopher J; Barwari, Temo; Hu, Jimiao; Hamborg, Thomas; Nevill, Alan; Hyndman, Samantha; Ansell, Valerie; Musa, Anntoniette; Jones, Julie; Goodby, Julie; Banerjee, Prithwish; O'Hare, Paul; et al.
Abstract : Aims: Cardiac resynchronisation therapy (CRT) is effective treatment for selected patients with heart failure (HF) but has 30% non-response rate. We evaluated whether specific biomarkers can predict outcome. Methods: A prospective single-centre pilot study of consecutive unselected patients undergoing CRT for HF between November 2013 and December 2015 evaluating cardiac extracellular matrix biomarkers and micro-ribonucleic acid (miRNA) expression before and after CRT assessing ability to predict functional response and survival. Each underwent three assessments (pre-implant, 6 weeks and 6 months postimplant) including: New York Heart Association (NYHA) class, echocardiography, electrocardiography, 6 min walk test (6MWT), Minnesota Living with Heart Failure Questionnaire (MLHFQ) and N-terminal pro-brain natriuretic peptide (NT-pro-BNP). Plasma markers of cardiac fibrosis assessed were: N-terminal pro-peptides of collagen I and III, collagen I C-terminal telopeptides (CTx) and matrix metalloproteinases (MMP-2 and MMP-9) as well as a panel of miRNAs (miRNA-21, miRNA-30d, miRNA-122, miRNA-133a, miRNA-210 and miRNA-486). Results: A total of 52 patients were recruited; mean age (±SD) was 72.4±9.4 years; male=43 (82.7%), ischaemic aetiology=30 (57.7%), mean QRS duration=166.4±23.5 ms, left bundle branch block (LBBB) morphology = 39 (75.0%), mean NYHA=2.7±0.6, 6MWT=238.8±130.6 m, MLHFQ=46.4±21.3 and left ventricular ejection fraction (LVEF)=24.3%±8.0%. Mean follow-up=1.7±0.3 and 5.8±0.7 months. There were 27 (55.1%) functional responders (3 no definable 6-month response; 2 missed assessments and 1 long-term lead displacement). No marker predicted response, however, CTx and LBBB trended most towards predicting functional response. Conclusion: No specific biomarkers reached significance for predicting functional response to CRT. CTx showed a trend towards predicting response and warrants further study. Trial registration number: NCT02541773 .